Indigenous melons (Cucumis melo L.) in Sudan: a review of their genetic resources and prospects for use as sources of disease and insect resistance - Mohamed, I.=700 1 Taha Yousif, M.
(En, Es, Fr)
ilus., 26 ref.
Keywords: CUCUMIS MELO; RECURSOS GENETICOS; RESISTENCIA A LA ENFERMEDAD; RESISTENCIA A LAS PLAGAS; ITALIA; MALON